Academic Writing Training for High School Students: Pelatihan Akademik Writing Bagi Siswa SMA - Paula Audry Rombepajung; Trully Christien Haenny Wungow; Yapi Hendrik Wongkar; St. Nur Aima Fatima; Nindy N. Ganap; Fergina Lengkoan; Amirudin Ais; Awaludin Rizal (Universitas Lancang Kuning, 2025)
Academic Writing Training for high school students is a program designed to improve students' ability to write good and correct academic papers. This program consists of several steps that can be taken, including an introduction to the concept of academic writing, developing writing skills, using references and sources, developing editing skills, using technology, developing presentation skills, developing peer review skills, developing writing skills for various disciplines, developing writing skills for various purposes, and developing writing skills for various sources. This training has several objectives, such as improving clear and logical writing skills, improving students' ability to organize ideas and structure their writing, improving students' ability to use effective and efficient language, improving students' ability to develop strong and logical arguments, and improving students' ability to develop effective communication skills. This training can be conducted using several effective and interactive methods, such as writing workshops, brainstorming, peer review, and others. In writing workshops, high school students are divided into groups and each group is given a specific topic to write about. After completing their writing, the groups will present their writing and receive feedback from teachers and classmates. In brainstorming, high school students are assisted by teachers to gather relevant ideas and analyze them critically. In peer review, high school students are divided into groups and each student is given a classmate's writing to monitor and provide feedback. Through this Academic Writing training, high school students can improve their ability to write good and correct academic papers, as well as enhance their skills in using technology and various disciplines. This training is crucial for several reasons, such as improving writing skills, critical thinking skills, organizing ideas, using references, editing skills, communication skills, becoming an independent learner, improving academic assignment skills, and developing character.